Nerve compression injury and increased endoneurial fluid pressure: a "miniature compartment syndrome". Issue 12 (December 1983) - Lundborg, G; Myers, R; Powell, H
Abstract : An inflatable miniature cuff was used to apply local compression of 80 mm Hg or 30 mm Hg to a segment of rat sciatic nerve for time periods varying from two to eight hours. The endoneurial fluid pressure was measured by direct micropipette measurement techniques at one or 24 hours after removal of the cuff, and the nerves were subjected to histological analysis. Endoneurial oedema, associated with a four-fold increase in endoneurial fluid pressure, was observed after compression at 80 mm Hg for four hours, and a three-fold increase was found after compression at 30 or 80 mm Hg for eight hours. Such an increase in endoneurial fluid pressure may interfere with intrafascicular capillary flow, and thereby constitute an important pathophysiological mechanism in nerve compression injuries.